EFEKTIVITAS FACE PRIMER BERBENTUK CREAM DAN SILIKON DALAM MENUNJANG KETAHANAN MAKEUP PENGANTIN PADA KULIT BERMINYAK - Mahisi, Widya Woro; Karyanto, Yunus; Mukti, Ria Andriani (Jurnal Tata Rias, 2025)
This study aims to describe the results of bridal makeup on oily skin types using facial primer cream, describe the results of bridal makeup on oily skin types using silicone face primer, and compare the two types of facial primer. This study uses a quantitative method with an experimental approach, involving 43 students of the Family Welfare Vocational Education Study Program as samples. Data collected through questionnaires and direct observation with the results of makeup using facial primer cream and silicone face primer. Furthermore, the analysis uses a normality test, homogeneity test, and hypothesis test (t test). The results of the study: 1) The results of the normality test show that the data is normally distributed with a significance value of the use of facial primer cream of 0.102>0.05 and facial silicone primer of 0.200>0.05 then. 2) The results of the homogeneity test get a significance result of 0.000 where from these results, the sig. value <0.05 then the data is declared not homogeneous. 3) The results of the hypothesis test (t-test) show a significant difference between the two types of primer, namely face primer cream users at 20.72 and for silicone face primer users at 25.35. The significance value of the t-test of 0.000 <0.05 indicates a difference between the two. With these results from the study, it shows that cream-based face primers are less effective in increasing the adhesion and durability of makeup on oily skin. Meanwhile, Silicon face primers provide more durable and matte results and Silicon Face primer is the main choice in bridal makeup for oily skin types than Face primer Cream. Keywords: Face primer, silicone, cream, oily skin, Makeup.